Las barriadas y la política de vivienda en las secuelas del terremoto del Cusco de 1950 - Pinley Covert, Lisa (Pontificia Universidad Católica del Perú, 2022)
This article examines the efforts to address the housing crisis in the aftermath of the 1950 earthquake in Cusco, Peru. Mid-twentieth-century Cusco served as an early incubator for ideas about affordable housing and development in Peru. Peruvian and foreign experts sought to rebuild Cusco as a beacon of modernity in the Andes. Still, for the most part, these global designs failed to come to fruition, leaving poor, working-class, mostly Indigenous cusqueños to improvise their own solutions. The article argues that this experience in Cusco helped shape housing policy in Peru more broadly.

Este artículo examina los esfuerzos por solucionar la crisis de vivienda a raíz del terremoto del Cusco de 1950. A mediados del siglo XX, esta ciudad sirvió como una incubadora de ideas en torno a una vivienda asequible y el desarrollo en el Perú. Expertos peruanos y extranjeros pretendieron reconstruir Cusco como una luminaria de modernidad en los Andes; sin embargo, la mayoría de estos diseños globales no se realizaron, y la clase pobre y obrera (indígenas cusqueños mayormente) tuvo que improvisar sus propias soluciones. Este trabajo propone que la experiencia cusqueña contribuyó en la formación de una política de vivienda nacional.
Barriadas and Housing Policy in the Aftermath of the 1950 Cusco Earthquake
Keywords: Housing; Shantytowns; Earthquake; Disasters; Developmentalism; Peru; Viviendas; Barriadas; Terremoto; Desastres; Desarollo; Perú; https://purl.org/pe-repo/ocde/ford#6.01.01